The Relationship between Physical Activity and Readiness for Childbirth in Pregnant Women at the Cimalaka Community Health Center, Sumedang Regency - Dinda Indika Putri; Emi Lindayani; Amanda Puspanditaning Sejati (LPPM STIKes Muhammadiyah Ciamis, 2026)
Birth preparation is an essential factor in reducing the risk of complications that may lead to maternal mortality during labor. Physical activity during pregnancy is believed to enhance maternal readiness for childbirth, both physically and psychologically. This study aimed to determine the relationship between physical activity and childbirth readiness among pregnant women at Cimalaka Primary Health Center, Sumedang Regency. This research employed a quantitative correlational design with a cross-sectional approach. The study population consisted of all pregnant women registered at the health center, with a total sample of 185 respondents selected through accidental sampling. Data were collected using the Pregnancy Physical Activity Questionnaire (PPAQ) to assess the level of physical activity and a childbirth readiness questionnaire. Data analysis included descriptive statistics to portray respondent characteristics and inferential analysis using the Spearman correlation test due to non-normally distributed data. The results showed a p-value of 0.074 (> 0.05), indicating that there was no significant relationship between physical activity and childbirth readiness. The correlation coefficient (r = 0.132) demonstrated a very weak positive relationship. These findings suggest that maternal readiness for childbirth is more strongly influenced by other factors, such as knowledge, access to information, previous childbirth experience, husband’s support, and participation in antenatal education classes, which may have greater cognitive and psychosocial impacts compared to daily physical activity.